2008
DOI: 10.2140/agt.2008.8.849
|View full text |Cite
|
Sign up to set email alerts
|

Co-contractions of graphs and right-angled Artin groups

Abstract: We define an operation on finite graphs, called co-contraction. Then we show that for any co-contraction y of a finite graph , the right-angled Artin group on contains a subgroup which is isomorphic to the right-angled Artin group on y . As a corollary, we exhibit a family of graphs, without any induced cycle of length at least 5, such that the right-angled Artin groups on those graphs contain hyperbolic surface groups. This gives the negative answer to a question raised by Gordon, Long and Reid.20F65, 20F36; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…Our main technical tool is the disk diagrams introduced in [CW04] (as "dissections of a disk") and further detailed in [Kim08]. We present the general theory here for the convenience of the reader.…”
Section: Disk Diagrams In Raagsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our main technical tool is the disk diagrams introduced in [CW04] (as "dissections of a disk") and further detailed in [Kim08]. We present the general theory here for the convenience of the reader.…”
Section: Disk Diagrams In Raagsmentioning
confidence: 99%
“…It is shown in [Kim08] that any disk diagram for w is dual in S 2 to a van Kampen diagram with boundary word w, and vice versa. In particular, given a disk diagram, one obtains a van Kampen diagram by simply taking its dual complex; see Figure 2.…”
Section: Disk Diagrams In Raagsmentioning
confidence: 99%
“…Theorem 1.3(1) also generalises the result of Kim-Koberda [10], which states that the linear forests P c 3 = P 1 P 2 (the symbol means the disjoint union), P c 4 = P 4 and C c 4 = P 2 P 2 have property ( * ). As a consequence of Theorem 1.3(1) and a result of Kim [9], we obtain the following result concerning embeddability between RAAGs on finite graphs whose underlying spaces are connected 1-manifolds. Theorem 1.4.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 66%
“…Several studies have demonstrated that the embeddability of RAAGs can be understood via certain graph theoretical concepts (e.g. [4], [5], [9], [10], [12] and [14]). In fact, theorems due to Kim and Koberda [10] state that the following for any finite graphs Λ and Γ.…”
Section: Introduction and Statement Of Resultsmentioning
confidence: 99%
“…In fact, Kim [Kim1] showed that A(P 1 (6)) contains A(C 5 ). On the other hand it is known [GS 2 ] that diagram groups cannot contain A(C n ) for odd n > 3.…”
Section: Introductionmentioning
confidence: 99%